Efektivitas Pengelolaan Kepegawaian Aparatur Kelurahan dalam Meningkatkan Kualitas Pelayanan Publik di Kelurahan Mangadu, Kabupaten Takalar - Henri; Nasir (STISIP Widyapuri Mandiri, 2026)
Quality public services are the main demands in the implementation of government, especially at the village level as a government unit that deals directly with the community. However, the quality of public services is often still faced with the problem of managing staff personnel that is not optimal. This study aims to analyze the effectiveness of the management of the personnel of the village apparatus in improving the quality of public services in Mangadu Village, Takalar Regency. This study uses a qualitative approach with a descriptive type of research. Data was collected through in-depth interviews, observations, and documentation of village officials and service user communities. The data analysis technique is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the management of the personnel of the village apparatus has been implemented, but it has not been fully effective. This is characterized by the limited number of apparatus, the mismatch between the placement of employees and competencies, and the lack of optimal coaching and development of apparatus. This condition has an impact on the quality of public services, especially in terms of speed and timeliness of services. Nevertheless, the attitude of the apparatus and the disclosure of service information are considered quite good by the public. This research contributes to the development of public administration science by strengthening the understanding of the importance of effective personnel management as a determining factor for improving the quality of public services at the village government level.